From Clinical Practice to Academic Student Instruction: Understanding the Clinical Instructor's Perspective Using a Mixed-Methods Approach. Issue 2 (June 2021) - Swart, Ruth; Hall, Marc
Background: Clinical instructors (CIs) are important to the provision of real-world experiential learning because they teach, mentor, and support students in clinical practice settings in higher education programs. CIs experience tensions that influence their retention and impact the sustainability of consistent, quality education for students. Purpose: The aim of this study was to examine the experiences of being a CI and how to better support them. Methods: CIs in a nursing faculty at a Western Canadian university were approached to participate. Data collection included a survey ( n = 17) with questions asking about the importance of and their ability to prepare, teach, and mentor nursing students in practice. Individual interviews ( n = 6) and a focus group ( n = 3) were conducted that asked CIs about their experiences and challenges. Analysis included descriptive statistics and thematic analysis. Results: Participants indicated feeling unprepared entering the instructor role. Key findings were the need to improve CI orientation so that it is more practical and meaningful, to increase peer support from other instructors, and to assist CIs' transition into becoming educators. Conclusions: Understanding CIs' assessment of their needs can help institutions better support and retain them, promoting consistency and quality in practicum instruction.